THaMES Evaluation Pipelines and Multimodal Model Robustness to Factual Caption Errors - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: What is the impact of THaMES evaluation pipelines on the robustness of multimodal models against factually incorrect captions in the ScienceQA dataset. 5 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.0/10. This report is a machine-generated literature synthesis and
Machine-generated literature synthesis.